Effectiveness of water treatment processes in removing precursors of chlorinated organic substances from mixtures of groundwater and surface water - Krupińska, Izabela (International Conference “Environmental Engineering”, 2026)
Due to the correlation of UV254 and UV272 absorbance with the formation of oxidation and disinfection by-products, it is a very important indicator in assessing the effectiveness of water treatment processes. The aim of this study was to determine changes in the value of UV254 and UV272 absorbance in water after successive treatment processes at the Water Treatment Plant in Poland near the city of Zielona Góra, which takes underground and surface water from the Obrzyca River. Mixed water was characterized TOC reached values from 7.80 to 8.23 mgC/dm3, DOC from 7.10 to 7.83 mgC/dm3, and UV254 and UV272 absorption from 19.34 to 20.38 m−1 and from 15.65 to 16.16 m−1. The treatment processes at the WTP near Zielona Góra include aeration of groundwater, microfiltration of surface water, coagulation of mixed water, sedimentation, filtration on catalytic-oxidative filter bed, filtration on dolomite filter bed and disinfection with chlorine dioxide. During technological studies carried out on a laboratory and technical scale, the following were tested as coagulant polyaluminum chloride with an alkalinity of 70% as well with an alkalinity of 85% which, in its composition, also contained iron. Analysis of the results showed that the highest reduction in UV254 and UV272 absorbance, by about 49 % and 53%, respectively, was obtained after coagulation with the polyaluminum chloride with 70% alkalinity, not containing iron compounds. It was also shown that both dolomite and catalytic-oxidative bed filtration increased the efficiency of removing precursors of oxidation and disinfection by-products. The dolomite bed increased the efficiency by about 7% (UV254) and about 9% (UV272) and the catalytic-oxidative bed increased the efficiency by about from 3 to 5% (UV254) and about from 3 to 4% (UV272).